THE USE OF SERIES OF PICTURE AS MEDIA TO IMPROVE STUDENTS' ABILITY IN READING NARRATIVE TEXTA QUASI EXPERIMENTAL STUDY OF SECOND GRADE STUDENTS AT SMA PASUNDAN CIKALONGKULON - Hayatun Nurlaila Rahmat, - (2011)
This paper entitled "The Use of Series of Pictures as Media to Improve Students' Ability in Reading Narrative Text: A Quasi Experimental Study of Second Grade Students at Private Senior High School in Cianjur." is aimed to test the hypothesis on the effect of series of pictures as a media in teaching reading narrative text and to find out the advantages and disadvantages of series of pictures in teaching reading narrative text. The population of this study is the eleventh grade students in Private Senior High School in Cianjur. The quasi experimental design is used as the research method. In addition, reading test was administered to obtain the data. The pretest was conducted before the treatment, while the posttest was conducted after the experimental group received the treatment. The finding indicates that series of picture as media was effective in improving students' reading ability. Therefore, the alternative hypothesis is accepted. It shows that series of pictures are effective to improve students' ability in reading narrative text. In further research, it is suggested to use series of pictures as media in teaching other genres